THE COMPLIANCE AND EFFECTIVENESS OF TUBERCULOSIS DRUG USE AT THE TALUN HEALTH CENTER IN CIREBON - Regar, Dhea Novakinanda; Zuniarto, Ahmad Azrul; Pandanwangi TW, Siti; Widianingsih, Nining (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb). This disease affects the lung organs and may also affect organs outside the lungs. This study aimed to determine the level of compliance and effectiveness of TB drugs, the relationship between compliance and effectiveness in using TB drugs, and the relationship between compliance and effectiveness based on socio-demographic data of the community. The research method used was descriptive observational, with retrospective data collection based on TB patient treatment cards. Compliance data were collected by completing the MMAS questionnaire, and effectiveness data were collected by recording sputum examination results using the SITB (Tuberculosis Information System) software. The sample comprised the total population according to these criteria. The technique used for sampling was total sampling, namely the total number of TB patients at Talun Health Center, Cirebon Regency, from November 2023 to April 2024, a total of 40 patients. Data analysis using the Spearman test consisted of compliance analysis, effectiveness analysis, the relationship between compliance and effectiveness, and the relationship between compliance and effectiveness based on socio-demographic data of the population. The results of the study showed that the level of compliance with TB drug use was 7.9 (medium level of compliance), and the effectiveness of TB drug use was 100%. There is a relationship between compliance and the effectiveness of TB drug use, but there is no relationship based on the socio-demographic data of the population. Keywords: Compliance, Effectiveness, TB Drugs